Stability of Protein and Oil Content in Soybean across Dry and Normal Environments—A Case Study in Croatia - Hrvoje Šarčević; Dario Iljkić; Zoe Andrijanić; Aleksandra Sudarić; Jerko Gunjača; Ivan Varnica; Mirta Rastija; Sara Godena; Marko Maričević; Domagoj Stepinac; Ivan Pejić (Agronomy, 2022)
Soybean is generally grown as a rainfed crop worldwide and very often is exposed to drought and high temperatures. The objectives of this study were to determine the performance and stability of 32 elite soybean genotypes for seed protein and oil contents across six dry and eight normal environments and to determine the influence of environment on the relationship between the two traits. In the combined ANOVA, genotypes (G), environments (E) and G × E were significant for both traits with protein content being more sensitive to environmental changes than oil content. Mean seed protein content decreased by 4.5% under drought conditions compared to normal ones and ranged from 2.3% to 7.1% for individual genotypes. At the same time drought caused a slight increase in seed oil content of +1.2%, with a range of −1.3% to +4.5% for individual genotypes. Genotype stability in terms of regression coefficient (b) and coefficient of variation (CV) was in moderate to weak negative correlation with mean genotype performance for protein content, while no correlation was observed between genotype stability and mean genotype performance for oil content. Protein and oil content were significantly negatively correlated in normal environments (r = −0.33), while no correlation between the traits was observed in dry environments (r = −0.02).